Atrial Functions and Aortic Elasticity in Children with Aortic Coarctation - Demirpence, Savas (Acta Cardiol Sin, 2015)
BACKGROUND: Coarctation of the aorta (CoA) is a chronic vascular disease characterized by a persistence of myocardial and vascular alterations. We aimed to evaluate children who have had successful coarctation surgery or balloon dilatation to evaluate the elasticity of the aorta, left atrial ejection force (AEF) and myocardial performance collectively at midterm follow-up. METHODS: Nineteen patients (7.15 ± 0.9 years of age) and 21 age-sex matched healthy children were included in this study. Left AEF index is defined as the product of mass and acceleration of blood expelled from the left atrium. Aortic stiffness and distensibility were estimated using ascending and descending aorta diameters. RESULTS: The left atrial force index [(g∙cm/s(2))/m(2)] in the patient group was found to be significantly higher (12.69 ± 7.29, 5.74 ± 2.59, respectively, p = 0.001). Distensibility of the ascending aorta (cm(2)/dynes 10(-6)) was significantly lower in the patient group than in the control group (42.13 ± 24.02, 78.79 ± 20.49, respectively, p < 0.001). The stiffness index of the ascending aorta was significantly higher in the patient group (p < 0.001). We also documented that atrial force index is associated with peak E velocity, right arm systolic blood pressure and left ventricular mass index. CONCLUSIONS: Our investigation showed that AEF is higher in children who have had successful coarctation surgery or balloon dilatation, and AEF is associated with systolic blood pressure, peak E velocity and left ventricular mass index. Distensibility of the ascending aorta was lower, and stiffness index was higher in children with corrected CoA than in healthy subjects.